“Assessment of the use of crossing structures by bears and other Mammals along the Egnatia Highway in Northern Greece.” - Δημητρά, Ελισάβετ; Dimitras, Elisabeth - Panayote (2015)
The expansion of transportation networks is making roads with vehicles as the more harmful direct human cause of animal mortality on land. The design and incorporation of wildlife crossing structures into road construction is a method which can mitigate these anthropogenic negative effects on wildlife. However, for most species, there is limited knowledge regarding effective and affordable crossing structure designs. We monitored ten crossing structures of the Egnatia Highway (NW Greece) in order to investigate whether wildlife, especially brown bears, use them as movement corridors. The monitoring was performed by means of motion activated wildlife cameras, during a 3-month autumn period (September-December). We found that all types of crossing structures are used by various native Mammals as well as by domestic (stray) animals. We investigated the influence of several factors on the effectiveness of each crossing, such as the dimensions of the structures, the surrounding vegetation, the land-use of the area, the human activity nearby and distance from natural or human resources. Regarding the bear which is the species of high conservation concern in our study, we found a positive correlation between the Openness Index and the probability of crossing the structure. Surprisingly our analysis showed that bears avoid crossings which are located near streams or rivers. As for other mammals, the use of crossing structures depends only on the distance from vegetation (in general) and the mean slope of entrances/exits (for wolves and dogs). Finally, we observed seasonal differences concerning the use of crossing structures by bears. Thus, seasonality on bear movements has to be taken into account for the design of future monitoring programs.